2005
DOI: 10.1590/s0100-879x2005000200014
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a 23-valent pneumococcal polysaccharide vaccine in Brazilian elderly

Abstract: Serum antibodies specific for the capsular polysaccharides of Streptococcus pneumoniae provide protection against invasive pneumococcal infection. In Brazil, this vaccine has been used for people over 65 years with clinical risk to develop pneumococcal infection since 1999. We evaluated the immune response of 102 elderly subjects (75.5% females and 24.5% males) with a mean age of 71 years, and 19 young healthy adults (63.2% females and 36.8% males) with a mean age of 27 years. The elderly study group consisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
(42 reference statements)
1
8
1
5
Order By: Relevance
“…In particular, serotype 3 was the most common serotype causing IPD in the elderly. Unlike the study by Simonsen et al [22], the present study showed PPSV23 induced good immunogenicity for serotype 3. Also, PPSV23 covers the most common serotypes causing IPD in the Korean elderly, except serotype 6A, which is thought to be highly cross-protected by vaccine serotype 6B [24].…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In particular, serotype 3 was the most common serotype causing IPD in the elderly. Unlike the study by Simonsen et al [22], the present study showed PPSV23 induced good immunogenicity for serotype 3. Also, PPSV23 covers the most common serotypes causing IPD in the Korean elderly, except serotype 6A, which is thought to be highly cross-protected by vaccine serotype 6B [24].…”
Section: Discussioncontrasting
confidence: 98%
“…Hammitt et al showed neither primary nor repeat vaccination elicited a significant increase in GMT to serotype 1 [21]. Simonsen et al indicated no increase in antibody concentration by ELISA for serotype 3 in both the elderly and young healthy adults [22]. Our study demonstrated GMTs in 12 vaccine serotypes, including serotypes 1 and 3, significantly increased after vaccination, which suggests functional antibody response after PPSV23 vaccination is generally satisfactory among the elderly.…”
Section: Discussionsupporting
confidence: 37%
“…Thus the percentages shown for serotype distribution in this age group are subject to a high degree of uncertainty Tätigkeitsberichte ing serum antibodies against ST 3, thereby preventing opsonisation which is necessary for phagocytosis of the encapsulated pneumococci [24]. Immunogenicity studies in adults have also shown significantly weaker immune response to ST 3 than to other serotypes for both PCV13 and PPSV23 [25][26][27][28]. In modelling the epidemiological effects of the vaccination (see Sect.…”
Section: Serotype Distribution Since Introduction Of Universal Infantmentioning
confidence: 99%
“…Pneumococcal polysaccharide vaccine containing only polysaccharide antigen, which is a T cell‐independent antigen, can induce serotype‐specific immunoglobulin (Ig)A, IgM, and IgG (mainly IgG2 subclass) antibodies and promote the killing of S pneumoniae by leukocytes and phagocytic cells, thus inducing specific protective effects. Immune responses to capsular polysaccharide are age‐dependent and serotype‐dependent 61,62 . Antibody levels initially increase after vaccination with PPSV23 and remain elevated for at least 5 years in healthy adults, but they do decline over time 63 .…”
Section: Pneumococcal Vaccinementioning
confidence: 99%
“…Immune responses to capsular polysaccharide are agedependent and serotype-dependent. 61,62 Antibody levels initially increase after vaccination with PPSV23 and remain elevated for at least 5 years in healthy adults, but they do decline over time. 63 Antibody levels in elderly people tend to decline to approximately baseline level within 7 years after vaccination.…”
Section: Immunogenicity and Persistencementioning
confidence: 99%